Psychological Aspects Among the Hearing Impaired Children - P. Vidyasagar; Mewa Singh (Journal of All India Institute of Speech and Hearing)
The study examines certain psychological aspects such as intelligence, memory, temperament and social functioning in the sensory neural and conductive hearing impaired groups as, compared with the mentally retarded and the normal control groups. Canonical discriminant function analysis resulted in the emergence of two discriminant functions which were named the "Affective" and the "Cognitive" dimensions. The sensory neural hearing impaired group manifested deficits on the affective dimension. No deficits were evident on the cognitive dimension in both the hearing impaired groups. The mentally retarded group manifested severe cognitive deficits. The findings provided several insights for habilitating and planning modes of intervention for the sensory neural hearing impaired.